EFFECTS OF LONG-TERM USE OF TOBACCO ON TASTE RECEPTORS AND SALIVARY SECRETION - Khan, Ghulam Jillani; Mehmood, Rashid; Din, Salah -ud-; Haq, Ihtesham -ul- (Journal of Ayub Medical College Abbottabad, 2003)
Background: Most of the methods of tobacco use are linked to the mouth, where the taste receptors, a primary site for stimulation of salivary secretion, are constantly exposed to tobacco. The main purpose of this study was to observe the effects of long-term use of tobacco on taste receptors and salivary flow rates. Methods: Subjects of the study were divided into smokers, pan, (tobacco-betel-lime quid) chewers, niswar (moist oral snuff) dippers and non-tobacco users as controls. Each group was comprised of 20 healthy male adults. The saliva of each subject was collected under resting condition and following application of crude nicotine and citric acid solutions to the tip of his tongue. Results: The appreciation of taste sensations perceived by each subject of each group was different for nicotine (bitter unpleasant burning sensations) than citric acid (sour burning sensations) but no subjective difference was observed among the corresponding groups. After stimulation with both nicotine and citric acid, all subjects of each group showed a significant rise (p<0.05) in their salivary flow rates but the increase was highly significant (p<0.005) in pan chewers only. Conclusion: We found that the taste receptors response and salivary flow rates of tobacco users were not much different from that of non-tobacco users. Therefore, we conclude that long-term use of tobacco does not adversely affect the taste receptors response and hence salivary secretion. Keywords: Tobacco, taste receptors, Saliva